2021
DOI: 10.26442/00403660.2021.04.200835
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of application of sorbed probiotics in complex therapy of pneumonia caused by SARS-CoV-2. Part 1. Heating clinical displays period

Abstract: Aim. To determine the clinical efficacy and safety of the sorbed probiotics Bifidobacterium bifidum 1 (5108 KОЕ) and B. bifidum 1 (5107 KОЕ) in combination with Lactobacillus plantarum 8P-А3 in the complex therapy of pneumonia caused by SARS-CoV-2 in adult patients without severe risk factors. Materials and methods. An open, randomized prospective study included 100 patients (45 men, 55 women), aged 18 to 60 years without risk factors for severe COVID-19 with pneumonia confirmed by computed tomography, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 25 publications
2
18
0
3
Order By: Relevance
“… 119 In addition, three studies noted the effectiveness of probiotics in treating diarrhea among COVID‐19 patients. 29 , 34 , 146 Similar studies have reported consistent results with our study that probiotics can treat gut dysbiosis and thus mitigate the GI symptoms arising from it. 155 , 156 One RCT conducted in China reported that the use of Bifidobacterium, Lactobacillus, Enterococcus , and Bacillus tablets was associated with a better immune function and reduced secondary bacterial or fungal infection.…”
Section: Association Between Covid‐19 Severity and Gut Microbiome Com...supporting
confidence: 91%
See 1 more Smart Citation
“… 119 In addition, three studies noted the effectiveness of probiotics in treating diarrhea among COVID‐19 patients. 29 , 34 , 146 Similar studies have reported consistent results with our study that probiotics can treat gut dysbiosis and thus mitigate the GI symptoms arising from it. 155 , 156 One RCT conducted in China reported that the use of Bifidobacterium, Lactobacillus, Enterococcus , and Bacillus tablets was associated with a better immune function and reduced secondary bacterial or fungal infection.…”
Section: Association Between Covid‐19 Severity and Gut Microbiome Com...supporting
confidence: 91%
“…The majority of the studies found the probiotics beneficial for COVID‐19 patients’ recovery. 29 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 45 , 70 , 76 , 77 One study evaluated the positive efficacy of FMT (Fecal microbial transplantation) for COVID‐induced GI upset. 33 Zhang et al reported that probiotics reduced the length of COVID‐19 illness and hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…У пациентов с синдромом раздраженной кишки пробиотики приводили к снижению степени депрессии и лимбической активности в ответ на отрицательные эмоциональные стимулы [30]. В первой части исследования, опубликованной ранее [20], помимо вероятного противовоспалительного эффекта, обсуждалась возможность косвенного влияния сорбированных пробиотиков на личностное восприятие симптомов. Получавшие ПС значительно реже отмечали одышку при физической нагрузке в своих дневниках (ОШ 0,09; 95% ДИ 0,02-0,04; р<0,001) по сравнению с получавшими стандартную терапию, хотя степень повреждения легких была умеренной.…”
Section: Discussionunclassified
“…В данном исследовании не проводили спирометрию после госпитализации, что можно отметить в качестве ограничения исследования. У 6 и 20% пациентов в параллельных группах отмечали увеличение степени поражения легких до КТ3-4 [20]. Средний уровень С-реактивного белка в момент выписки из стационара оставался умеренно повышенным: 21,2±15,0 и 27,3±20,0 мг/л (р>0,05) в сравниваемых группах соответственно.…”
Section: Discussionunclassified
See 1 more Smart Citation